La participation des jeunes dans une association de protection de l’enfance : des logiques d’action en tension - Valérie Becquet; Pascal Fugier; Ruggero Iori (Sociétés et Jeunesses en Difficulté)
This article looks at the conditions and process of participation of vulnerable young people within a child protection organization. The research carried out on these young people mainly focuses on care management, trajectories within institutions and transitions towards autonomy. This article analyses participation in formal and informal arrangements in order to better understand the tension between public action norms, appropriation by social workers and young people trajectories. Based on the case of a local non-profit organization offering child protection, specialized prevention, professional training and insertion activities, we will show the issues at stake in participation and the tensions that emerge from four rationale for action: civic, management, normative and clinical.